Effect of Environmental Change on the Welfare Status of Crop Farmers in Kaduna State and Federal Capital Territory, Nigeria - Ajunwa, Chikezie Gabriel; Aluwong, Jeremiah Samuel; Haruna, Ojuh Ezekiel; Ayodele, Josephine Titilayo; Abah, Michael Oguche; Eboh, Kennedy Chinedu; Idisi, Park Odojoma; Alabi, Olugbenga Omotayo (Nepalese Journal of Agricultural Sciences, 2026)
This study investigated the effect of environmental change on the welfare status of crop farmers in Kaduna State and Federal Capital Territory, Nigeria. A multi-stage sampling technique was used to select 198 crop farmers. Primary data were used based on a well-structured questionnaire. The data were analyzed using descriptive statistics, farmer household income exchange, Foster, Greer, and Thorbecke (FGT), and the Probit model analysis. The results show that the mean age was 49 years with approximately farm experience of 12 years. The on-farm household income (74.41%) is the dominant source. The largest expenditure is on production cost (46.97%) reflecting the significant investment required for agricultural activities. Furthermore, majority of the farm households (61.90%) have an income greater than their expenditures, this suggests that they have their welfare condition enhanced. Approximately, 43 (79.63%) of the farm households without secondary income fell below the poverty line. About 161 (81.31%) of the farm households with both primary and secondary incomes were below the poverty line. The significant socio-economic factor and environmental change that influence the welfare status of crop farmers include age, number of years spent in school education, total crop output, change in temperature, reduction in the size of water bodies, and heat waves. The study recommended that climate-smart agriculture training, subsidies for drought-resistant maturing crop varieties should be provided by Government and non-government organizations and establish localized community-based early warning systems in collaborating with NiMet (Nigerian Meteorological Agency) to provide farmers with real-time planting and harvesting schedules.